Gas Turbine Combined Cycle Power Plants - Gülen, S. Can, 1962- (Boca Raton : CRC Press LLC, 2019)
This book covers the design, analysis, and optimization of the cleanest, most efficient fossil fuel-fired electric power generation technology at present and in the foreseeable future. The book contains a wealth of first principles-based calculation methods comprising key formulae, charts, rules of thumb, and other tools developed by the author over the course of 25+ years spent in the power generation industry. It isfocused exclusively on actual power plant systems and actual field and/or rating data providing a comprehensive picture of the gas turbine combined cycle technology from performance and cost perspectives. Material presented in this book is applicable for research and development studies in academia and government/industry laboratories, as well as practical, day-to-day problems encountered in the industry (including OEMs, consulting engineers and plant operators).
8.3.2 Optimum Combined Cycle Efcfiiency8.4 History; 8.5 State of the Art; 8.6 The Hall of Fame; 8.6.1 Irsching; 8.6.2 Bouchain; 8.6.3 Inland Empire Energy Center; 8.6.3.1 Steam-Cooled H Technology; 8.6.3.2 IEEC 107H; 8.6.3.3 Fuel Gas Moisturization; 8.6.4 60% Net (LHV) Bogey; 8.6.5 Epilogue; References; Chapter 9 Major Equipment; 9.1 Gas Turbine Package; 9.2 Steam Turbine Package; 9.2.1 Steam Valves; 9.2.2 Steam Seal Regulator (SSR); 9.2.3 Gland Seal Condenser (GSC); 9.2.4 Turning Gear; 9.2.5 Protective Features; 9.3 Heat Recovery Steam Generator (HRSG); 9.4 AC Generator; 9.5 Scope of Supply
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: SCIENCE / Energy; SCIENCE / Mechanics / Dynamics / Thermodynamics; TECHNOLOGY / Engineering / Civil; Gas-turbines.; Electric power production; Electric generators